Failure correction in time‐modulated linear arrays. Issue 3 (1st March 2014) - Poli, Lorenzo; Rocca, Paolo; Oliveri, Giacomo; Massa, Andrea
Abstract : A technique for failure correction in time‐modulated linear arrays is presented. Starting from the knowledge of the array elements with failures, the on–off behaviour of the switches at the other elements is properly reconfigured to radiate a pattern as close as possible to the ideal one in terms of pattern features. The array reconfiguration is carried out by solving an optimisation problem through the minimisation of a suitable cost function proportional to the mismatch between ideal and reconfigured pattern features. Representative results are reported and discussed to illustrate the effectiveness of the proposed approach as well as to assess the robustness to failures of time‐modulated arrays thanks to their real‐time reconfigurability.